Compreendendo estratégias e barreiras para a adoção da governança digital em estados brasileiros - Santos, Fábio Pinheiro dos (2018)
This research has as its main theme Digital Governance, with focus on strategies and barriers for its adoption in the context of Brazilian Public Administration. In this study, Digital Governance is the way that governments use the Information and Communication Technologies to deliver to all people convenient information and governmental services, to better the quality of those services and to provide bigger possibilities of the citizen’s participation. In this setting of transformation of the relations between government and society, organizations need to use well defined strategies regarding actions and projects for its implementation. However, given the complex environment that involves the public sector, barriers and obstacles are met in the face of initiatives that have as an objective the Digital Governance. Thereby, with the intention of understanding the challenge to be faced by the Brazilian Public Organizations, a documental analysis on the Politics and on the Digital Governance Strategy released by the Brazilian Federal Government in 2016 was made, as well as the evolution of the strategic indicators for the period of 2016 and 2017 was evaluated. Afterward, with the objective of understanding the barriers to be faced by the managers of technological areas, in State Public Organizations, regarding the initiatives that aim the availability of public information, the prospecting and betterment of Digital Public Service and the enlargement of the societies’ participation in the cycle of Public Politics, 25 semi structured interviews were performed. Representatives of São Paulo, Rio de Janeiro, Rio Grande do Sul, Paraná, Santa Catarina States and Federal District also participated in this research. As results, it’s possible to highlight the mechanisms used by the Brazilian Federal Government in trying to transform the Electronic Government into Digital Governance, which is close to the concept of Collaborative Governance. It’s also highlighted that the State Governments, even before elaborating their politics and strategies for the adoption of Digital Governance, have already faced cultural and structural barriers before their Information Access Initiatives, Digital Public Services and Social Participation. In this context, an assembly of twelve structural and eight cultural barriers were identified and understood. This research contributes to the theorization of Digital Governance, in the context of the Brazilian Public Administration, and contributes with the public managers in the identification of difficulties to be met for the implementation of actions that aim at the purpose of Digital Governance.